2016
DOI: 10.1021/acs.nanolett.5b04715
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Materials Discovery for Electronic and Thermoelectric Properties of Single-Molecule Junctions

Abstract: We have investigated a large set of symmetric and asymmetric molecules to demonstrate a general rule for molecular-scale quantum transport, which provides a new route to materials design and discovery. The rule states "the conductance GXBY of an asymmetric molecule is the geometric mean of the conductance of the two symmetric molecules derived from it and the thermopower SXBY of the asymmetric molecule is the algebraic mean of their thermopowers". The studied molecules have a structure X-B-Y, where B is the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 49 publications
0
71
0
Order By: Relevance
“…As an example, from a measurement of the conductance of 1 in Figure and from knowledge of the magic numbers of 1 and 2 , the conductance of 2 could be predicted ahead of its synthesis. Finally, we note that weak coupling, locality, connectivity, mid‐gap transport and phase coherence can be utilized to yield further quantum circuit rules, which relate the transport properties of molecules of the form A‐B‐C, B‐A‐C and B‐C‐A . Such rules are also useful for the purpose of materials discovery, since from measurements of the electrical conductance or Seebeck coefficient of two such molecules, the electrical and thermoelectrical properties of a third can be predicted.…”
Section: Resultsmentioning
confidence: 95%
“…As an example, from a measurement of the conductance of 1 in Figure and from knowledge of the magic numbers of 1 and 2 , the conductance of 2 could be predicted ahead of its synthesis. Finally, we note that weak coupling, locality, connectivity, mid‐gap transport and phase coherence can be utilized to yield further quantum circuit rules, which relate the transport properties of molecules of the form A‐B‐C, B‐A‐C and B‐C‐A . Such rules are also useful for the purpose of materials discovery, since from measurements of the electrical conductance or Seebeck coefficient of two such molecules, the electrical and thermoelectrical properties of a third can be predicted.…”
Section: Resultsmentioning
confidence: 95%
“…[13] Following theoretical predictions of the introduction of DQI effects due to interactions of pendant oxygen and bipyridene groups with conjugated molecular cores [14] as well as subsequent experimental confirmation, [15] as tudy of QI effects in molecular junctions of p-conjugated systems was carried out by GuØdon et al using the conducting atomic force microscopy technique. [16] Arroyo et al studied QI effects in acentral phenyl ring by varying the coupling to av ariety of anchor groups. [17] Manrique et al have also demonstrated tuning of QI effects through heteroatom substitution within amolecular core,a nd proposed aq uantum-circuit rule for designing molecular devices and materials.…”
Section: Introductionmentioning
confidence: 99%
“…C) Comparison between the thermopowers S XBY and the arithmetic means ( S XBX + S YBY )/2 for different molecules. Reproduced with permission . Copyright 2015, American Chemical Society.…”
Section: Thermoelectric Properties Of Molecular Junctionsmentioning
confidence: 99%